2018
DOI: 10.3389/fneur.2018.00785
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Integration Environment as an Advanced Prosthetic Limb Training Platform

Abstract: Background: Despite advances in prosthetic development and neurorehabilitation, individuals with upper extremity (UE) loss continue to face functional and psychosocial challenges following amputation. Recent advanced myoelectric prostheses offer intuitive control over multiple, simultaneous degrees of motion and promise sensory feedback integration, but require complex training to effectively manipulate. We explored whether a virtual reality simulator could be used to teach dexterous prosthetic control paradig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…The VIE allows individuals to direct the movements of a virtual avatar using surface electromyogram (sEMG) signals captured from their residual limbs, digitized through an electrically-isolated data acquisition system, and filtered using signal analysis algorithms. Our laboratory has previously described the utility of the VIE in training individuals with upper extremity amputation in this pattern recognition platform for prosthetic control 21 , 22 . Motions included hand open, wrist flexion, extension, pronation, and supination, several user-selected grasps, “no movement”, and elbow flexion and extension with trans-humeral amputation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The VIE allows individuals to direct the movements of a virtual avatar using surface electromyogram (sEMG) signals captured from their residual limbs, digitized through an electrically-isolated data acquisition system, and filtered using signal analysis algorithms. Our laboratory has previously described the utility of the VIE in training individuals with upper extremity amputation in this pattern recognition platform for prosthetic control 21 , 22 . Motions included hand open, wrist flexion, extension, pronation, and supination, several user-selected grasps, “no movement”, and elbow flexion and extension with trans-humeral amputation.…”
Section: Methodsmentioning
confidence: 99%
“…Signal feature extraction and motion classification occurred using machine learning-based pattern recognition software and a Linear Discriminant Analysis classifier. The same software interfaces are used to control the MPL prosthesis 17 , 21 , 22 .…”
Section: Methodsmentioning
confidence: 99%
“…While these activities can be completed with a physical prosthetic device, training in a virtual environment has shown to be an effective way to train amputees to use their device (Phelan et al, 2015;Nakamura et al, 2017;Perry et al, 2018;Nissler et al, 2019). Training in a virtual environment can be a cost effective way for clinics to perform rehabilitation (Phelan et al, 2015;Nakamura et al, 2017) and help prosthesis users learn how to manipulate their device using its particular control scheme (Blana et al, 2016;Woodward and Hargrove, 2018), and gamifying rehabilitation has been shown to increase a prosthesis user's desire to complete the program (Prahm et al, 2017(Prahm et al, , 2018.…”
Section: Background Clinical Outcome Assessmentsmentioning
confidence: 99%
“…Putrino et al [76] trained two nonhuman primates (Macaca mulatta) to use the virtual prosthetic and observed that they performed reaching and grasping tasks. The authors describe virtual prostheses as highly versatile and Perry et al [77] have demonstrated that a virtual reality (VR) training platform can be used to efficiently train upper extremity amputees. In this study, thirteen active-duty military personnel with 14 upper extremity amputations learned to control a virtual avatar over 1 to 2 months.…”
Section: Advanced Rehabilitation: Augmented and Virtual Realitymentioning
confidence: 99%